Be Healthe for Your Heart: Protocol for a Pilot Randomized Controlled Trial Evaluating a Web-Based Behavioral Intervention to Improve the Cardiovascular Health of Women With a History of Preeclampsia - Taylor, Rachael; Shrewsbury, Vanessa A.; Vincze, Lisa; Campbell, Linda; Callister, Robin; Park, Felicity; Schumacher, Tracy; Collins, Clare; Hutchesson, Melinda (Frontiers in Cardiovascular Medicine, 2019)
Background: Women with a history of preeclampsia are at greater risk of cardiovascular disease (CVD) related morbidity. Despite this knowledge, there is a lack of interventions available for women with a history of preeclampsia for the prevention of CVD. The aim of this pilot randomised controlled trial (RCT) is to determine the acceptability and preliminary efficacy of a web-based behavioural intervention targeted to women with a history of preeclampsia (Be Healthe for your Heart). Method: Australian women aged 18 to 45 years, with a recent history (≤ 4 years post diagnosis) of preeclampsia will be recruited for a 3-month, 2-arm parallel group pilot RCT. Participants will be randomised into 2 study arms: 1) Be Healthe for your Heart or; 2) Control, with assessments conducted at baseline, and after 3-months. Be Healthe for your Heart is an intervention delivered online via the program website, with weekly emails to support changes in modifiable CVD risk factors (excess body weight, physical inactivity, poor diet and stress), using behaviour change techniques (e.g. self-monitoring, goal setting). Intervention acceptability (satisfaction, usability, appropriateness and usage) and impact on absolute full CVD 30-year risk score, CVD risk markers and modifiable risk factors will be assessed. Discussion: No studies to date have evaluated acceptability and preliminary efficacy of a web-based intervention for the prevention of CVD in this high-risk population with preeclampsia. This pilot trial will inform development of a fully powered RCT if acceptability and preliminary efficacy are demonstrated.